Market orientation and the performance of airports in Europe’s peripheral areas - Halpern, Nigel (Cranfield University, 2006)
As a consequence of deregulation in the airline industry, market forces rather than public service considerations increasingly dictate services to and from airports in Europe’s peripheral areas. The new market advocates market-driven management practices as a means of satisfying airline customers and implies that airports that adopt a more marketorientated approach than their rivals will perform better. This study investigates the theoretical foundations of a market orientation, which can be defined as the organisationwide generation, dissemination and response to market intelligence. The main aim of this study is to examine the relationship between market orientation and the performance of airports in Europe’s peripheral areas. The research methodology was implemented using a questionnaire-based survey that was administered to the managers of 217 airports in 17 different countries. Usable responses from 86 airports were received and analysed. The findings of this study suggest that airports wishing to outperform competitors can do so by adopting a market orientation and should seek to continually monitor and improve the way in which they gather, disseminate and respond to market intelligence. This will be particularly effective when market turbulence is high and/or when the focus of the airport is on developing leisure services. In addition, market orientation was found to have a positive effect on performance because it means that airports are more likely to be innovative in their approach to marketing. This means that airport managers should try to develop a market-orientated culture with innovative marketing practices in mind, and visa versa. The fact that independently-owned airports have significantly higher levels of market orientation than regionally-owned or nationally-owned airports suggests that independent ownership is more conducive to the development of a market orientation. The findings of this study do have a number of limitations, the most notable being that they are restricted to airports in Europe’s peripheral areas. It is recommended that future research should be conducted on airports worldwide in order to investigate differences between a wider range of airport types and geographical regions. In addition, the findings of this study suggest that a stakeholder orientation is important for airports seeking to improve their performance, especially smaller airports that are publicly-owned. It is recommended that future studies should investigate antecedents to and consequences of a stakeholder orientation. Future studies should also investigate whether a stakeholder orientation has a greater effect on performance than a market orientation does, and whether the two types of orientation complement each other.
Keywords: Europe’s peripheral areas; Deregulation of European air transport markets; Market orientation; Airport marketing performance